2021
DOI: 10.1038/s41598-021-87761-3
|View full text |Cite
|
Sign up to set email alerts
|

Extra virgin olive oil improved body weight and insulin sensitivity in high fat diet-induced obese LDLr−/−.Leiden mice without attenuation of steatohepatitis

Abstract: Dietary fatty acids play a role in the pathogenesis of obesity-associated non-alcoholic fatty liver disease (NAFLD), which is associated with insulin resistance (IR). Fatty acid composition is critical for IR and subsequent NAFLD development. Extra-virgin olive oil (EVOO) is the main source of monounsaturated fatty acids (MUFA) in Mediterranean diets. This study examined whether EVOO-containing high fat diets may prevent diet-induced NAFLD using Ldlr−/−. Leiden mice. In female Ldlr−/−.Leiden mice, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…In people with type 1 diabetes mellitus (DM1), EVOO has been associated with an improvement in weight, waist circumference [ 186 ], lipid profile [ 187 ], and quality of life [ 188 ]. Lastly, polyphenol-rich EVOO has maintained insulin secretion and insulin sensitivity during a high-fat diet in animal models [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In people with type 1 diabetes mellitus (DM1), EVOO has been associated with an improvement in weight, waist circumference [ 186 ], lipid profile [ 187 ], and quality of life [ 188 ]. Lastly, polyphenol-rich EVOO has maintained insulin secretion and insulin sensitivity during a high-fat diet in animal models [ 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oleuropein and hydroxytyrosol can reduce adipocyte hyperplasia and hypertrophy, by inhibition of adipogenesis-related genes in human cell lines [ 305 , 306 ] and stimulation of mitochondrial biogenesis-related genes in murine adipocytes [ 307 ]. When fed high-fat diets, EVOO-supplemented mice underwent lower weight gains [ 189 ], and they showed less metabolic, inflammatory, and microbiota disruption [ 308 ], as well as more modest subcutaneous and visceral fat development—in relation to a higher basal energy expenditure proportional to their weight—which could be explained by a higher expression of Ucp genes in muscle and visceral fat [ 309 ]. Regarding BMI reduction, a meta-analysis of clinical trials calculated statistically significant improvements for food enrichment with phytosterols and phytostanols in dyslipidemic, overweight, and obese subjects [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overproduction of oxidative species induces the inflammatory response [61], and this response is accompanied by a reduction in antioxidant capacity [62], which promotes the activation of HSCs and liver damage. Other studies suggested a higher gene expression of antioxidant enzymes in response to a liver ROS overproduction, in order to counteract the oxidative stress [63,64]. Besides, oxidative stress-induced hepatic damage is also affected by imbalance of other enzymes, such as iNOS, whose gene levels are highly expressed in HFD-induced NASH models [65].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial function in the clearance of cholesterol by the liver [ 119 ]. LDLR deficient rodents have been used to establish models of NAFLD [ 120 , 121 ]. In those models, elevations in hepatic neutral and hepatic proinflammatory oxylipins were observed [ 122 ].…”
Section: Discussionmentioning
confidence: 99%